The Influence Of Exchange Rate And Freight Cost Toward Export Volume Adidas - Adelia Regita Putri; Endang Sulistiyani; Paniya Paniya (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
Exports volume of Adidas from time to time is not stable because the amount always fluctuates and shows the decrease every year. This study aims to determine the effect of the exchange rate and freight cost partially and simultaneously on the export volume of Adidas at PT Apparel One Indonesia 1. This research uses an explanatory research type with a quantitative approach. The data used in this study is secondary data from documentary research and observation. The data comes from PT Apparel One Indonesia 1 and Bank Indonesia from January 2014 to December 2019. The sampling technique that used was purposive sampling with the number of samples are 72 data. The output of this study shows that exchange rate and freight cost affect export volume simultaneously and are able to explain the changes of export volume for 44,5%. Meanwhile, partially, the exchange rate variable has a negative and significant effect on the export volume of Adidas. The freight cost variable has a negative and significant effect on the export volume of Adidas. Exchange rate variable has dominant influence toward export volume.